HUBUNGAN POSTUR KERJA DAN MASA KERJA DENGAN KELUHAN MUSCULOSKELETAL DISORDERS PADA PENGADUK JENANG X DI DUSUN DODE, KABUPATEN MAGELANG - Luthfi Achmad Hariadi; Muchamad Rifai (Institut Kesehatan dan Teknologi Al Insyirah, 2021)
ABSTRACT Complaints of Musculoskeletal Disorders experienced by jenang mixer workers are caused by continuous work. This study was conducted to determine whether work posture and working period can affect workers who complain of Musculoskeletal Disorders. The sample in this study amounted to 36 people. The instrument used to analyze work posture with complaints of Musculoskeletal Disorders is the Rapid Entry Body Assessment, while to view complaints of Musculoskeletal Disorders using the Nordic Body Map sheet. The conclusion of this study is there is a relationship between working period and complaints of Musculoskeletal Disorders stirrer with a p value of 0.010 (p value>0.05), and there is no relationship between work posture with complaints of Musculoskeletal Disorders on jenang mirasa stirrers in Dode Hamlet, Gulon Village, Salam District, Magelang Regency stirrer with a p value of 0.481 (p value <0.05).